ВТОРОТО РАМНИШТЕ НА СЛОЖЕНОСТ КАЈ МУЛТИПЛИКАТИВНИТЕ СЛОЖЕНИ СЕМАНТЕМИ ОД ПРВ СТЕПЕН ВО МАКЕДОНСКИОТ ЈАЗИК - Violeta Janusheva (Philological Studies, 2019)
The paper presents models of multiplicative first level semantemes from second class of complexity and determines the formal indicators of these structures for expressing multiplicative aspect configuration. The relevant feature of multiplicative aspect configuration – event/situation comprehension as a moment is stressed out, as well as the mutual relations between these semantemes with the habitual and telic aspect configuration which are connected with polysemy of the semantemes as a result of the context role, real or assumed.